Micro-patterned NiFe2O4/Fe–TiO2 composite films: Fabrication, hydrophilicity and application in visible-light-driven photocatalysis. Issue 17 (1st December 2020) - Duan, Zongfan; Zhu, Yu; Hu, Zhudong; Zhang, Jingyu; Liu, Dongjie; Luo, Xia; Gao, Minghao; Lei, Li; Wang, Xianhui; Zhao, Gaoyang
Abstract: The micro-patterning of NiFe2 O4 (NFO) films was achieved by a photolithography-assisted chemical solution deposition technique without photoresists. Subsequently, the micro-patterned NFO films were combined with Fe 3+ -doping TiO2 (FTO) films and then novel micro-patterned NFO/FTO composite films were prepared. The structures, morphologies, hydrophilicity, and optical and visible-light photocatalytic performance of the micro-patterned NFO/FTO films were investigated. The results revealed that the micro-patterned NFO/FTO films exhibit the entire visible-light absorption, lower recombination of electrons and holes and improved hydrophilicity, resulting in higher visible-light photocatalytic activity for methylene blue degradation as compared to pure NFO and FTO films. In addition, the hydrophilicity and photocatalytic activity of the micro-patterned NFO/FTO films are strongly dependent on their pattern periods. More interestingly, the recyclability of the micro-patterned NFO/FTO film can be easily realized without the assistance of external magnet, and the catalytic activity does not decrease with cycle numbers.